Effect of Temperature and Humidity on the Degradation Rate of Multicrystalline Silicon Photovoltaic Module - N. C. Park; W. W. Oh; D. H. Kim (International Journal of Photoenergy)
In a PV module, the relative humidity (rh) of a front encapsulant is different from that of a backside encapsulant (rhback). In this study, the effective humidity (rheff) in a PV module was investigated to study the effects of moisture variation on the degradation rate (RD). rheff represents uniform humidity in a PV module when it is exposed to certain damp heat conditions. Five types of accelerated tests were conducted to derive the relation between rheff and rhback. rheff showed a linear relationship with rhback at constant temperature. Two types of models, namely, Eyring and Peck models, were used for predicting the RD of PV modules, and their results were compared. The RD of PV modules was thermally activated at 0.49 eV. Furthermore, the temperature and rheff history of PV modules over one year were determined at two locations: Miami (FL, USA) and Phoenix (AZ, USA). The accumulated RD values based on the temperature and rheff of the modules were calculated by summing the hourly degradation amounts over the time history.